Perancangan Ontologi Produk Fashion Lokal Sebagai Representasi Pengetahuan Pakaian Wanita - Putu Athalia Reyna Sanjaya; I Made Widhi Wirawan (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2026)
Local Fashion Industry in Indonesia has experienced a rapid growth, especially in the women’s clothing segment. Nonetheless, challenges related to data standardization and product information connectivity obstruct visibility and effective product search. To address these issues, this study aims to design an ontology for local women’s fashion products using the Methontology approach and Semantic Web technologies. The ontology represents key entities such as fashion products, brands, sizes, materials, and usage categories, along with the structured relationships among them. The development process utilizes Protégé and Web Ontology Language (OWL), and is validated using SPARQL queries to explore semantic knowledge. The results show that the developed ontology successfully organizes knowledge of local fashion products in a systematic and queryable structure. This ontology is expected to serve as a foundation for semantic search systems and product recommendation platforms to promote and strengthen the presence of Indonesian local fashion brands.